IL-10 AND IL-35 AS INFLAMMATION REGULATORS IN PATIENTS WITH ALLERGIC RHINITIS AND MILD ATOPIC ASTHMA (American International Journal of Biology and Life Sciences, 2022)
Background. Significantly less is known about the immunoregulative cytokines, especially in allergic airway disease. This study aims to present the involvement of IL-35 and IL-10 in patients with allergic rhinitis (AR) and allergic bronchial asthma (BA). Methodology. The study comprised 71 patients –AR, patients with concomitant AR and mild atopic BA, and healthy controls (HC). We examined the serum levels of IL-35 and IL-10, along with other instrumental examinations, between March and September 2021. Findings. Levels of the regulatory cytokines IL-35 and IL-10 were significantly lower in patients than in HC (87.19±11.90 vs. 96.12±1.79 pg/ml; and 30.26±17.55 vs. 111.56±65.03 pg/ml, respectively). Furthermore, threefold higher serum IL-10 levels were found in healthy subjects compared to patients (p = 0.006). No difference in the levels of interleukins was found between the studied groups. Conclusions. Our results indicate that elevated IL-35 and IL-10 may play an essential role in reducing the activity of underlying allergic inflammation in allergic respiratory diseases, although no difference in the levels of the studied cytokines was found between the different groups of patients. Therefore, we can speculate that the immunosuppressive cytokines IL-35 and IL-10 were involved in maintaining the healthy state of no inflammation.